Manusia Dan Sejarah Pada Masa Islam (Studi Kasus: Masjid Majan Sebagai Bentuk Perkembangan Islam di Tulungagung) - Mohammad Didi Hardiansyah; Nadya Rifa’atul Kanin; Annisa Rif’atul Husniah; Saiqotul Fauziah; Achmad Akyas Roychan; Hany Nurpratiwi (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
Humans as actors of history in which history cannot be separated from humans, history cannot be said to be history if there are no humans. Islam developed very well in the archipelago through traders who came from various countries. Islam is also well developed in the Java region, especially in Tulungagung. The development of Islam in Tulungagung is developing very well, this is indicated by the development of Islamic-based learning centers such as the establishment of modern Islamic boarding schools, namely madrasas. The establishment of madrasas cannot be separated from the sequence of historical events and support from every community. In addition, the establishment of this madrasa was also sparked by Islamic clerics and broadcast Islamic religion to the public. This paper aims to explore and provide an overview of how the development of Islam in Tulungagung from its inception to its development to date. The method used in this study uses the literature review method. In the research it was found that human intervention was very influential in the development of the history of the entry of Islam to Tulungagung. Islam entered the Tulungagung region and received a positive response from the community by seeing the departure of the Islamic religion and the majority of people in Tulungagung who embraced Islam.